Solve f(g(x) where x = 3 f(x) = 2x + 3 g(x) = 3(x+2)
It is important to first identify where the g(x) needs to be substituted in the f(x) equation. In this case f(x) = 2(g(x)) + 3 Thus, f(x) = 2(3(x+2)) + 3 Then, with x = 3 you plug it into the equation and solve for f(x). f(x) = 2(3(3) + 6) + 3 (Remember to apply the rule of distribution) f(x) = 2(9 + 6) + 3 f(x) = 30+3 f(x) = 33
What is the past tense of "You were hungry" in plural?
Vous aviez faim.
What are the three principle questions that economist look at to study and analyze economics, people, and the market?
What, Whom, and How?